Effects of bacteriophages on biofilms formed by Staphylococcus aureus isolated from patients with orthopedic infection - Gordina E.M.; Bozhkova S.A.; Smirnova L.N. (Клиническая микробиология и антимикробная химиотерапия, 2022)
Objective.